Redescription of Phalotris labiomaculatus (Serpentes, Dipsadidae, Elapomorphini), with notes on the taxonomic boundaries within the nasutus group - Hamdan, Breno; Da Silva, Nelson Jorge Jr; Silva, Helder Lucio Rodrigues (Zootaxa, 2013)
Phalotris labiomaculatus Lema, 2002 was described based on a single specimen from Porto Franco, south of the Brazilian state of Maranhão, being rediscovered three years later in Mateiros, a municipality in the north of the state of Tocantins, attesting to its occurrence in the cerrado of both banks of the Tocantins River. The discovery of 28 new specimens from other localities during field expeditions (2009–2011) allowed a redescription of the species, adding new data on meristic and morpho-qualitative traits. These results enable a better diagnosis of intraspecific, ontogenetic and sexual variation, consolidating its taxonomic relationships with other species belonging to the nasutus group. The distribution map of P. labiomaculatus, as well as an identification key to the species of the natusus group, are provided. The type-locality is fixed to the municipality of Porto Franco, state of Maranhão.